Sharp Extensions of a Cusa-Huygens Type Inequality - Bagul, Yogesh J.; Chesneau, Christophe (Armenian Journal of Mathematics, 2024)
In this article, we propose an extension and generalization of a Cusa-Huygens type inequality and thus refine an existing inequality in the literature. As an application, we extend the improved Shafer's inequality for the arctangent function.
Keywords: Cusa-Huygens Type Inequality; Sharp Bounds; l'Hospital's Rule of Monotonicity